(3efY GdefGRYGJ GdYfjaI (B:s (3GSJQGJjLjI ddOHdheGSjI GdhbGFjI (B/s - (3dhfO, eGjcds; (3YGOds ((3GdbGgQI (B:s (3GdLeYjI GdeUQjI dfTQ GdeYQaI h GdKbGaI GdYGdejI ,s, 1999)
(3Gf acQI efY GdNdGaGJ ef GdJMhd Gdi GdefGRYGJ YfjaI h GdJj jecf GdJYHjQ YfgG HYHGQI GdOHdheGSjI GdhbGFjI gj acQI LPGHI h NGUI aj YGde jOQc fOQI GdehGQO GdeJGMI dehGLgI GdGReGJ GdEbdjejI h ZjQgG eeG jgOO GdGef h jHOh Gf JONd WQa KGdK GHYO GKQG h Gbd JcdaI EPG Je bHd Gf JTJZd GdGReGJ h dcf eGPG JYfj GdOHdheGSjI GdhbGFjI HGdJMOjO h eJi h cja jLH Gf JSJNOe Gf GdJMdjd GdTGed GdhGQO aj gPG GdcJGH jYQa GdE fPGQ GdeHcQ h GdOHdheGSjI GdhbGFjI h Jbje Ydi VhA GSJYQGV GdYOjO ef GdLghO GdhbGFjI GdMOjKI ef GdPj jbhe HgG hhSGFdgG h jHjf cja JSJWjY GdcjGfGJ eJYOOI GdGWQGa h GdbhejI Gf JJZdH Ydi GdJMOjGJ GdJj fhGLg GdGLQGAGJ GdhbGFjI GdaYGdIs
(3JQLeI d(B: Preventing violent conflitss
Keywords: (3EOGQI GdUQGYs; (3JShjI GdHGSajcjI ddfRGYGJ GdOhdjIs; (3GdeaGhVGJ GdOHdheGSjI aj GdefGRYGJ GdOhdjI s